Recognition of a status acquired abroad: Sweden - Vaige, Laima (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
This report addresses questions of civil status recognition in Sweden, the main legal developments and case-law related to the recognition of a civil status. The ECHR and CJEU case law influenced the case-law some extent, especially in relation to cross-border recognition of names and surrogacy arrangements. Meanwhile, autonomous private international law on recognition of marriages prefers substantive Swedish law and protects the Swedish approach to children’s rights and gender equality.